Software Testing Tools Covering WinRunner, SilkTest,LoadRunner, JMeter, TestDirector and QTP with Case Studies - PUSULURI NAGESWARA RAO (Dreamtech Press New Delhi, 2012)
With C D
Keywords: Software Testing